Removal of Phosphate by Paper Mill Sludge: Adsorption Isotherm and Kinetic Study - Mohamad, Sharifah; Abu Bakar, Nor Kartini; Ishak, Ahmad Razali; Surikumaran, Hemavathy; Pandian, Kavirajaa; Ramachandran, Muggundha Raoov; Mohamad Zain, Nur Nadhirah; Chandrasekaram, Kumuthini (Asian Publication Corporation, 2014)
Phosphate ions have been removed from aqueous solution by paper mill sludge. The influences of experimental conditions such as pH, amount of adsorbent, initial concentration of phosphate, adsorption isotherm and adsorption kinetics of paper mill sludge were studied. The adsorption of phosphate was more efficient in the basic pH region (pH 12). Pseudo second-order model fits better than the pseudo first-order model for adsorption kinetic data and indicates the adsorption process is based on chemisorptions. The calculated activation energy (Ea) is 37.01 J/mol which further suggests that the sorption of phosphate by paper mill sludge was based on chemical adsorption. Consequently, the equilibrium isotherm data were fitted well to Langmuir isotherm with maximum adsorption capacity of 12.65 mg/g. From the study, it showed that paper mill sludge has the potential to be utilized as a cost effective and high capability adsorbent for removal of phosphate from aqueous solutions.